EVALUASI POTENSI HEPAR SEBAGAI SUMBER ENZIM PLATELET ACTIVATING FACTOR ACETYLHIDROLASE (PAF-AH) PADA PROSES ATEROGENESIS - Retno Susilowati (Lembaga Penelitian dan Pengembangan Universitas Islam Negeri Maulana Malik Ibrahim Malang., 2012)
The atherogenesis is a fairly complicated process that deposit cholesterol in wall of arterial blood. Pathogenic atherosclerotic plaque formation requires very long time and it is often called as the silent killer. PAF-AH is a proatherogenic enzyme whose levels in serum rise rapidly since the beginning of the process atherogenesis. The sources of PAF-AH other than macrophages in the atherosklerostic plaque not been widely studied. The liver is the organ where the place of lipid metabolism and susceptible to oxidative stress. Oxidized Lipids serve as a stimulator of the synthesis of PAF-AH, so it needs to be explored its potential as a source of PAF-AH. This study aims to evaluate the liver as the source of PAF-AH on atherogenesis process that occurs in mice. This research was conducted based on post Test Control Design.This research is to observe PAF-AH levels in the lysates serum and liver. Histological observations of the presence of PAF-AH enzymes in liver tissue with the Immunohistochemistry are also observed in normocholesterol mice than hypercholesterolemic rats’ diet for 30 days. Data were analyzed with Anova test and correlation analysis. The results showed that hyperclolesterolemia rats had higher levels of PAF-AH in serum than normocholesterolemia mice (408.35 ± 142.23 218.93 ±106.07 ng /ml). Hypercholesterolemia mice had higher levels of PAF-AH in the liver lysate than normocholesterol mice (554.81 ± 143.33 275.60 ± 89.68 ng/ml). PAF-AH levels in serum correlate with levels in serum, PAF-AH liver lysate is more than the levels in serum. Immunohistochemistry show that enzyme PAF- AH found in liver tissue constituent cells.